Differential Treatment in Environmental Law: Addressing Critiques and Conceptualizing the Next Steps. Issue 2 (24th October 2016) - Cullet, Philippe
Abstract: Differential treatment in international environmental law is the broader manifestation of the principle of common but differentiated responsibilities (CBDRs). It reflects equity concerns that have underlain most environmental debates on a North-South basis for several decades. Over the past two decades, various forms of differentiation have been introduced in environmental law instruments to the point where it has become an essential element of any international environmental agreement. At the same time, differential treatment has been the object of sustained criticism, arguing that it should be temporary, that it fails to target beneficiaries appropriately, and undermines environmental outcomes. This article takes the opposite view and argues that differentiation remains crucial in a world where widespread inequalities remain. Beneficiaries need to be identified on the basis of environmental and social indicators and differentiation should constitute the basis on which environmental measures are adopted. Worsening environmental conditions and an evolving global context call for adding new elements to the existing framework for differentiation. This requires thinking beyond the current structure centred around nation states and conceptualizing differentiation around common heritage equity. It also requires expanding differentiation beyond the field of environmental law, to include all areas of sustainable development law. Further, differential treatment needs to be implemented in a way that benefits the most disadvantaged in every country. These measures are necessary to foster a vibrant international environmental law which addresses the equity needs of all states in years to come.